ST 22-AB : phase 2 Study of lethal threat of rebound/ricochet concrete debris due to accidental explosion - Yap, Teik Lynn (2016)
In the world, there are only two debris hazard distances (i.e. safety distances) for structures storing explosives. Very little study has been done in the area of how concrete further breaks up upon impact after an accidental explosion. This phenomenon contributes significantly to the debris pick-up data and the determination of debris hazard distance. This study hence aims to study the post-ground impact effects of concrete after an accidental explosion so that we can better study the safety distances and if we can reduce this distance because of our space constraints in built-up city states like Singapore.